Posttransplant cyclophosphamide as GVHD prophylaxis in patients receiving mismatched unrelated HCT: the PHYLOS trial - Anna Maria Raiola; Benedetto Bruno; Antonio Maria Risitano; Federico Mosna; Irene Maria Cavattoni; Francesco Onida; Giorgia Saporiti; Francesca Patriarca; Marta Lisa Battista; Vincenzo Pavone; Anna Mele; Patrizia Chiusolo; et al. (Blood Advances)
Abstract: Posttransplant high-dose cyclophosphamide (PTCy) is effective in overcoming the negative impact of HLA disparity in the haploidentical setting. In light of these results, we investigated the efficacy of PTCy, in improving clinical outcomes of hematopoietic stem cell transplantation (HSCT) from a mismatched unrelated donor (MMUD) in patients with acute myeloid malignancies by reducing the incidence and severity of acute graft-versus-host disease (aGVHD). A prospective, single-arm, phase 2 study (PHYLOS) was conducted by the Gruppo Italiano Trapianto di Midollo Osseo. The ethical committees of the participating centers approved the study (EURODRACT 2017-003530-85). A total of 77 consecutive patients (acute myeloid leukemia: 64; myelodysplastic syndrome: 13) were enrolled at 26 Italian transplant centers (January 2020-November 2022). Median age of the patients was 53 (range, 19-65) years. The 100-day cumulative incidence of grades 2 to 4 aGVHD was 18.2% (95% CI, 10.6-27.6) and of grades 3 to 4 was 6.5% (95% CI, 3.1-15.1). Seventy-one patients (92%) had full-donor chimerism with complete neutrophil engraftment by day +30. One-year cumulative incidence of chronic GVHD was 13.4% (95% CI, 6.9-22.1). One-year cumulative incidence of nonrelapse mortality was 9.1% (95% CI, 4.0-16.9), and the relapse rate was 23.8% (95% CI, 14.9-33.9). One-year overall survival and graft relapse-free survival were 78.6% (95% CI, 67.4-86.3) and 55.3% (95% CI, 43.4-65.7), respectively. Our study in a homogeneous patient cohort suggests that PTCy leads to a low rate of aGVHD and improves clinical outcomes of HSCT from MMUD. This trial was registered at www.clinicaltrials.gov as #NCT03270748.